Beyond Acute Appendicitis: Insights into the Diverse World of Appendix Pathology - Arpana Dharwadkar; Aakriti Kundlia; Vidya Vishwanathan; Yamini Ingale; Tushar Kamble (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background Appendiceal conditions continue to present diagnostic challenges due to their variable clinical presentations and the complex interplay of demographic factors. This study aims to provide a thorough analysis of the prevalence, gender distribution, and histopathological characteristics of appendiceal conditions with more attention toward mucinous lesions. Methods A detailed examination of 380 appendectomy specimens was conducted, encompassing demographic and histopathological data. Clinical diagnoses, radiological findings, and histopathological results were scrutinized to identify trends and challenges in diagnosing appendiceal conditions. Results The study unveiled a significant prevalence of appendectomies within the “21-30 years” age-group, with a pronounced male predominance (62.63%). The most prevalent diagnosis was “Acute Appendicitis” (66.32% of cases), followed by “Chronic Appendicitis” (27.37%). Notably, mucinous lesions represented 1.57% of cases, with a distinct female predominance. All six cases were reported as low-grade appendiceal mucinous neoplasm (LAMN). LAMN was the common mucinous neoplasm in our study clinically presenting as acute abdomen and radiology having varied diagnosis. It accounted for 1.57% of cases with female predominance. Mucinous lesions presented with diverse clinical and radiological characteristics and were mostly diagnosed incidentally during appendectomy. The definitive diagnosis of rare mucinous lesion was achieved through histopathological analysis. Conclusion While the main cause for acute abdomen is acute appendicitis, this study emphasizes the necessity of histopathological analysis to achieve precise diagnoses of appendiceal conditions, particularly mucinous lesions that can masquerade as acute conditions. The study emphasizes the challenges in diagnosing mucinous lesions accurately in cases with varied clinical and radiological presentations, underlining the indispensable role of histopathological examination. The findings affirm the pivotal role of histopathology in ensuring accurate clinical management and treatment decisions.